Direct Growth of Triple Cation Metal-Organic Framework on a Metal Substrate for Electrochemical Energy Storage - Mohd Zain N.K.; Vijayan B.L.; Misnon I.I.; Das S.; Karuppiah C.; Yang C.-C.; Yusoff M.M.; Jose R. (My University, 2025)
Metal-organic frameworks (MOFs) offer a robust structure with high surface area together with open metal center sites which easily undergo the reversible redox reaction without damaging the framework; therefore, they are actively considered as a medium for electrochemical energy storage. This article demonstrates the superiority of triple cation metal-terephthalate as charge storage electrodes over their single component counterparts. We report the preparation of ternary metal-terephthalate (CoCuNi-bdc/NF) containing equimolar precursors of Co, Cu, and Ni as metal centers and terephthalic acid (H 2 bdc) as the organic linker and its single metal counterparts (Co-bdc/NF, Cu-bdc/NF, and Ni-bdc/NF) on Ni-foam substrate via a one-step facile hydrothermal reaction. The structure and morphologies of the CoCuNi-bdc/NF composite and its single component counterparts are characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and field-emission scanning electron microscopy techniques. The charge storage capabilities of the electrodes are evaluated by cyclic voltammetry, charge-discharge cycling, and electrochemical impedance spectroscopy in an aqueous alkaline electrolyte (6 M KOH) in a three-electrode system (half-cell) configuration. The specific capacity of CoCuNi-bdc/NF was ∼321.3 mA h g -1 (∼2892 F g -1 ), which is over 50% larger than the best performing single metal-terephthalate, Co-bdc/NF (∼208.2 mA h g -1 1874 F g -1 ), followed by Cu-bdc/NF (∼171.3 mA h g -1 ∼1542 F g -1 ), and last Ni-bdc/NF with ∼143.3 mA h g -1 (∼1290 F g -1 ). The specific capacity of CoCuNi-bdc/NF ranges from ∼191.9-321.3 mA h g -1 (∼1727-2892 F g -1 ) as current density varied from 40 to 1 A g -1 with ∼77% retention at 10 A g -1 and ∼59% at 40 A g -1 . CoCuNi-bdc/NF displays better electrochemical performance compared to its single component MOFs; hence, CoCuNi-bdc/NF could be the promising electrode material for supercapacitor materials. In the long term, this research would be expandable to a wide range of functional transition-organometallic materials for an energy storage paradigm. © 2018 American Chemical Society.